PROFIL PASIEN STROKE ISKEMIK AKUT DENGAN TERAPI RECOMBINANT TISSUE PLASMINOGEN ACTIVATOR DI RSUP DR. KARIADI SEMARANG - Retnaningsih Retnaningsih; Theodorus Kevin Hendartono (NEURONA, 2019)
PROFILE OF ACUTE ISCHEMIC STROKE PATIENTS WITH RECOMBINANT TISSUE PLASMINOGEN ACTIVATOR THERAPY IN DR. KARIADI HOSPITAL SEMARANGABSTRACTIntroduction: The use of recombinant tissue plasminogen activator (rtPA) is recommended within 4.5 hours from onset, with door to needle (DTN) time <60 minutes, so that it will decrease morbidity and mortality rates.Aims: To evaluate the evaluate the profile of acute ischemic stroke patients with rtPA therapy in Dr. Kariadi Hospital Semarang.Methods: This was a descriptive study by looking at medical records of patients with acute ischemic stroke with onset less than 4.5 hours performed rtPA therapy in Dr. Kariadi Hospital Semarang during Januari 2017 until May 2018.Results: There were 36 patients, 19 (52.8%) male, 17 (47.2%) female. Age range from 36 to 74 years with stroke onset 15-180 minutes. There were lacuner ischemia in 29 patients (80.6%) and teritorial ischemia in 7 patients (19.4%). The mean DTN time 67.22 ± 12.29 with DTN time for rtPA >60 minutes was performed in 23 (63.9%) patients and <60 minutes in 13 (36.1%) patients. The mean NIHSS on admission 8.67±3.51; The mean NIHSS within first 24 hours 6.94±3.25; The mean NIHSS on discharge 5.64±5.50. The mean Barthel Index on admission 57.97±19.27, and The mean Barthel Index on discharge 73.33±26.25.Discussion: There was an improvement of NIHSS and Barthel Index in acute ischemic stroke patients with rtPA therapy. The mean DTN time still >60 minutes, so that service system improvements are needed in order to improve clinical outcomes of acute ischemic stroke patients with rtPA therapy (DTN time <60 minutes).Keywords: Barthel Index, NIHSS, recombinant tissue plasminogen activator (rtPA), ischemic stroke, door to needle (DTN)ABSTRAKPendahuluan: Pemberian recombinant tissue plasminogen activator (rtPA) direkomendasikan dalam waktu sampai 4,5 jam dengan waktu door to needle (DTN) <60 menit agar dapat menurunkan tingkat morbiditas dan mortalitas pada stroke iskemik akut.Tujuan: Untuk mengetahui profil pasien stroke iskemik akut dengan terapi rtPA di RSUP Dr. Kariadi Semarang.Metode: Penelitian deskriptif dengan melihat rekam medis pasien-pasien stroke iskemik akut periode Januari 2017 hingga Mei 2018 dengan onset kurang dari 4,5 jam yang mendapatkan terapi rtPA di RSUP Dr. Kariadi Semarang.Hasil: Dari 36 subjek, didapatkan proporsi laki-laki lebih banyak dari pada perempuan (52,8% vs 47,2%) dan rerata usia 58±8,63 tahun. Rerata waktu awitan adalah 92,5±42,79 menit dengan tipe iskemik lakuner (80,6%) dan rerata waktu DTN 67,22±12,29 menit.  Rerata NIHSS 24 jam pertama adalah 6,94±3,25 yang menurun menjadi 5,64±5,50 saat keluar RS. Rerata Indeks Barthel subjek saat masuk RS adalah 57,91±19,27 yang meningkat saat keluar menjadi 73,33±26,25.Diskusi: Terdapat perbaikan nilai NIHSS dan Indeks Barthel pada subjek stroke iskemik akut yang mendapatkan terapi rtPA. Rerata waktu DTN adalah >60 menit, menunjukkan perlunya perbaikan sistem pelayanan untuk meningkatkan luaran klinis pasien stroke iskemik akut dengan DTN <60 menit.Kata kunci: Door to needle, Indeks Barthel, NIHSS, recombinant tissue plasminogen activator, stroke iskemik